Wilhelminische Bürger und „germanische Arier“ im Spiegel des „Primitiven“ –: Ambivalenzen einer Mimikry an die kolonialen ‚Anderen’ - Bruns, Claudia (Comparativ, 2009)
Wilhelmine Citizens and “Germanic Aryans” in the Mirror of the “Primitive” – Ambivalences of a Mimicry of the Colonial ‘Other’ Towards the end of the nineteenth century, ethnology was on the threshold of being established as a university discipline. Anthropologists and ethnographers endeavored to lend the new discipline stronger legitimacy and to explain its relevance to their contemporaries. The function of the “primitive” in all this was in many respects ambivalent. On the one hand, from an evolutionist perspective, the social order of indigenous peoples marked an earlier stage of development within a long civilizing process that culminated in western societies. To the degree that the indigenous Other was declared to be the origin and likeness of the western Self, however, the difference between the “primitive” beginning and the “civilized” end melted away. While the discourse on male societies (Männerbund) – which was continued in the “ritualist school” of German studies and archaeology at the University of Vienna – claimed to have discovered universally applicable types, thus implying a fundamental sameness between European and non-European cultures, that very discourse also propagated the racial uniqueness of the “Germanic Aryan,” which stood in direct contradiction to the assumption of universality. Following Homi Bhabha, my contribution is concerned less with dismissing such ambivalences as irrational and absurd than with identifying them as integral components of the colonial discourse and uncovering their mechanics and effects.